Investigating the Effect of Quality of Work Life on Organizational Commitment (Case Study: Technical Affairs Staff Of South Oil Fields Company) - Seyed Abdolhosein Nabavi; Soheila Lashkari (توسعه اجتماعی)
One of the most important motivational issues that have spread widely in the study of industrial and organizational psychology today is the issue of organizational commitment. Organizational commitment is an effective factor in organizational behavior of employees and the efficiency of organizations. This article has been written with the aim of investigating the effect of quality of work life on organizational commitment. In the theoretical dimension, to achieve the objectives of the research, the combined theory of Homans exchange has been used. The research was conducted by survey method and using a questionnaire among all the technical affairs staff of the South Oil Fields Company in 2015. In this research, stratified sampling method proportional to volume and simple random has been used. The most important results of the research showed that; There is a significant relationship with organizational commitment between all components of quality of work life except (adequate pay, safe work environment, growth opportunity in the organization in addition, there is a significant relationship between demographic variables including age , education level and organizational position with organizational commitment. But there is no significant relationship between gender variables with organizational commitment.